Taxonomia de Stenochironomus Kieffer, 1919 (Chironomidae, Diptera) na Amazônia Central, Brasil - Dantas, Galileu Petronilo da Silva (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
The genus Stenochironomus Kieffer, 1919 (Diptera: Chironomidae) has more than a hundred described species and has a worldwide distribution, occurring in a11 biogeographical. regions except Antarctica. The larvae of a11 known species of the genus are miners of submerged leaves or wood in severa1 freshwater habitats. In Brazil there are 17 known species, 14 of which are from Amazon region. In order to describe the imrnature stages of previously described species and describe new species, collections were carried out in streams i . the municigalities of Presidente Figueiredo, Itacoatiara, Novo Airão and Manaus. Leaves and wood mine& by Stenochironomus larvae were collected and transported to the laboratory where they were kept to obtaifi the adults. Eleven species was collected, seven of which was new for the science, seven new species were found, three of which were described i . a11 stages, three as male andpupa and two only as male. In addition, were described the female and the immaturr: stages" of S. impendes Borkent, the pupa of S. zonarius Borkent and the female of S.palliacu1ea.t~~ Borkent. Identification keys for adults from Neotropical region and for pupae and larvae from Amazoriia region were proposed.
Keywords: Stenochironomu; Taxonomia; Chironomida; insetos aquáticos